Strategi Pengembangan Wisata Halal di Kabupaten Kuningan Berdasarkan Analisis SWOT (Strengths, Weaknesses, Opportunities, Threats) - Eva Siti Ropiah (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2025)
This study aims to analyze the feasibility of developing halal tourism in Kuningan Regency, West Java, through a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis approach. Kuningan Regency has great potential to be developed as a leading halal tourism destination based on the natural wealth, culture, and religiosity of its people. The research method used is descriptive qualitative with data collection through literature studies, observations, and related document reviews. The results of the analysis show that Kuningan Regency has strengths in the form of natural beauty, local wisdom, and strong religious values; but faces weaknesses in supporting infrastructure, halal certification, and trained human resources. Development opportunities are wide open with global halal tourism trends and supportive national policies, although faced with the challenges of competition with other halal tourism destinations and sustainability issues. The implications of this study indicate the need for an integrated halal tourism development strategy by involving all stakeholders to achieve the status of a sustainable leading halal tourism destination.